Molecular Modeling, Dimer Calculations, Vibrational Spectra, and Molecular Docking Studies of 5-Chlorouracil - Akalın E.; Çelik S.; AKYÜZ, SEVİM (Springer, 2020)
The structure and vibrational calculations of 5-chlorouracil (5-ClU) and its most stable dimer have been analyzed using the DFT method with B3LYP/6-31++G(d,p) and wb97xd/6-31++G(d,p), respectively. Vibrational calculations of the monomeric and dimeric forms were performed using both harmonic and anharmonic oscillator approximations with the same basis sets. A complete vibrational analysis of the molecule has been performed by combining experimental Raman, FT-IR spectral data and quantum chemical calculations. In addition, the DNA docking analysis of 5-ClU molecule was performed. A 5-ClU molecule binds to the active site of DNA by hydrogen bonding interactions. The results show that the docked ligand formed a stable complex with DNA with binding affi nity of –5.3 kcal/mol.
Keywords: 5-Chlorouracil; Dimeric Structure; Molecular Docking; Density Functional Theory; Vibrational Spectroscopy